2015
DOI: 10.5465/amj.2013.0303
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Over-Emergence in Self-Managing Teams: The Role of Gender and Countervailing Biases

Abstract: We examine leadership over-emergence, defined as instances when the level of one's leadership emergence is higher than the level of one's leadership effectiveness, in a sample of intact self-managing teams who worked together for a period of seven months. We draw from Gender Role Theory and Expectancy Violation Theory to examine the role of gender in predicting leadership over-emergence. Building on arguments from Gender Role Theory, we find that all else equal, men over-emerge as leaders. However, Expectancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(196 citation statements)
references
References 81 publications
9
185
2
Order By: Relevance
“…Despite substantial evidence establishing that leader effectiveness is composed of both task‐oriented and socially‐oriented components (Judge, Piccolo, & Ilies, ; Stogdill, ), the current results suggest that exhibiting concern for others, sensitivity, and other communal proclivities makes one less likely to emerge as a leader, on average. Our finding that communion is devalued when making leader emergence judgments helps to explain recent research showing that women tend to underemerge as leaders given their levels of leadership effectiveness (Lanaj & Hollenbeck, ). These authors speculated that although individuals generally recognize communal behaviors as contributing to group success, these same behaviors do not, “trigger automatic perceptions of leadership emergence” (p. 1488).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Despite substantial evidence establishing that leader effectiveness is composed of both task‐oriented and socially‐oriented components (Judge, Piccolo, & Ilies, ; Stogdill, ), the current results suggest that exhibiting concern for others, sensitivity, and other communal proclivities makes one less likely to emerge as a leader, on average. Our finding that communion is devalued when making leader emergence judgments helps to explain recent research showing that women tend to underemerge as leaders given their levels of leadership effectiveness (Lanaj & Hollenbeck, ). These authors speculated that although individuals generally recognize communal behaviors as contributing to group success, these same behaviors do not, “trigger automatic perceptions of leadership emergence” (p. 1488).…”
Section: Discussionsupporting
confidence: 62%
“…In a comprehensive review of the gender‐leadership emergence literature, Eagly and Karau () found that men emerged as leaders more often than did women, yet evidence suggests that this gender gap in leader emergence is not due to gender differences in leader effectiveness (Lanaj & Hollenbeck, ; Paustian‐Underdahl, Walker, & Woehr, ). Because leadership emergence refers to “whether” and “to what degree” an individual is perceived as a leader by others (Judge, Bono, Ilies, & Gerhardt, ), the gender difference in leader emergence paints a troubling picture of the preconceptions women must overcome to obtain leadership roles.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analyses conducted by Eagly and Karau (1991) confirms this: men were more likely than women to emerge as leaders, although in another meta-analytical study both were found to be equally effective (Eagly, Karau, & Makhijani, 1995). Recent research has indeed found that men over-emerge (or inappropriately emerge) as leaders -that is chances of men becoming leader of a group when in fact they should not is greater than women (Lanaj & Hollenbeck, 2015). This discrepancy is suggested to be due to the social stereotypes of the role of men and women which create a barrier and a negative bias for women as leaders (Eagly & Karau, 2002;S.…”
Section: Biological Sex Gender and Leadershipsupporting
confidence: 54%
“…Having an understanding of implicit bias including workplace practices is also essential. Women are urged to understand and overcome gender bias (Lanaj and Hollenbeck, 2015); however, many women are not even aware when bias is occurring (Crosby, 1984, 1986). …”
Section: Developing Women Who Persist and Succeedmentioning
confidence: 99%